New records of helminths of Sceloporus pyrocephalus Cope (Squamata, Phrynosomatidae) from Guerrero and Michoacán, Mexico, with the description of a new species of Thubunaea Seurat, 1914 (Nematoda, Physalopteridae) - Garduño-Montes de Oca, Edgar Uriel; López-Caballero, Jorge D.; Mata-López, Rosario (ZooKeys, 2017)
A total of 61 specimens of the Red-headed Spiny Lizard Cope (Phrynosomatidae) collected during the breeding season (June/July 2003, 2004 and 2005) from Western Mexico were examined for helminths. The morphological characterization of the helminths found was made through light microscopy and scanning electron microscopy. Nine taxa of helminths were identified, two cestodes: sp. and sp., and seven nematodes: Garduño-Montes de Oca, Mata-López & León-Règagnon, 2016, Garduño-Montes de Oca, Mata-López & León-Règagnon, 2016, sp., Physalopterinae gen. sp., Caballero-Rodríguez, 1971, Caballero, 1938 and a new species of Seurat, 1914. Larvae of sp. and Physalopterinae gen. sp. were found in the body cavity and digestive tract, respectively. Excluding the species of Chatterji, 1933, is recorded for the first time as a host of the remaining seven taxa of helminths. Additionally, sp. n. is described and illustrated as a new nematode species, parasite of from Mexico. This new species can be differentiated from the majority of its congeners by the absence of spicules, the particular pattern of caudal papillae in males and the small ratio of oesophagus length:male total body length (0.1-0.16).